Revisiting ROS: duality in organ aging progression - Mohan Yu; Shiyi Liu; Chenxin Zhang; Wen Yang (Molecular Biology Reports, 2026)

Wastewater antibody signatures reflect SARS-CoV-2 infection and immunization patterns in the population - Dhammika Leshan Wannigama; Mohan Amarasiri; Phatthranit Phattharapornjaroen; Cameron Hurst; Charin Modchang; John Giles; Jillian Gauld; Tanakorn Chantanasaro; Kazuhiko Miyanaga; Longzhu Cui; Stefan Fernandez; Hirotake Mori; et al. (Water Research, 2026)

Key enzymes and genetic traits in sulfur autotrophic denitrification: Electron donors, functional microbes, and applications - Guangtian Song; Yanhe Han; Ziying Wei; Yang Xu; Haoyi Wang; Mengxiang Wei; Mohan Li; Xuejiao Ma; Bowen Liu; Zaixing Li (Bioresource Technology, 2026)

Underestimation of matrix-bound aflatoxin B1 in pressed peanut cake: Investigating the binding and dissociation mechanisms - Mohan Li; Chenhao Jiang; Gang Yang; Kewei Chen; Muying Du; Zsolt Zalán; Sameh Awad; Jianquan Kan (Food Chemistry, 2026)

Hollow kapok fiber-enabled photothermal aerogel with water supply and salt back-diffusion for solar desalination and thermoelectric generation - Shuyue Feng; Yao Wang; Bingyan Wang; Li Wang; Mohan Yang; Lixin Feng; Heng Li; Shaotian Qi; Ankang Jia; Yanfang Zhao; Kun Chen; Wei Xia (Chemical Engineering Journal, 2026)

Construction of chemical looping gasification model based on machine learning: focusing on performance prediction, feature importance and parameter optimization - Juan Zhao; Mohan Yang; Yadong Ge; Zhi Wang; Beibei Yan; Jianwu Zhang (Waste Management, 2026)

Electrode-assisted biodegradation of methylparaben (MEP): A sustainable approach for efficient degradation and toxicity management - Pavithra Muthukumar Sathya; Harshavardhan Mohan; Gwang-Min Lee; Hee-Jong Yang; Do-Youn Jeong; Byung-Taek Oh (Environmental Research, 2026)

Geochemical and microbial functional responses of surface soil to simulated low-concentration CO2 leakage from geological storage - Junqing Sun; Xiaoyu Han; Xiaojun Sun; Huaxiu Qin; Di Yang; Mohan Shangguan; Jinren Lu; Haoshuai Li; Yang Li; Mutai Bao (Environmental Research, 2026)

Uncertainty analysis of DNAPL migration model in low-permeability media based on Bayesian stacking - Yue Pan; Mohan Yang; Jianwei Dou; Beiyi Xu; Feng Zhou; Wenyi Xie (Stochastic Environmental Research and Risk Assessment, 2026)

Reinforcing electrolyte skeleton via in-situ cross-link enhancement for solid-state lithium metal batteries - Ziwen Tian; Mohan Yang; Yutao Wang; Qiwei Wu; Yu Guan; Hao Men; Yali Li; Lian Wang; Yuefeng Su; Yong Zhao (Chemical Engineering Journal, 2026)

Microplastics in simulated digestion: Surface modifications, enzyme interference, and chemical migration - Gopinath Mummaleti; Samuel O. Ogundipe; Toshifumi Udo; Joon Hyuk Suh; Anand Mohan; Zwe Ling Kong; Laurie J. Reitsema; Yang Jiao; Fanbin Kong (Food Chemistry, 2026)

Life cycle assessment of membrane electrochemical systems for ammonia nitrogen recovery from wastewater - Fadhel H. Alrabiah; Kai Yang; Mohan Qin; Andrea L. Hicks (Water Research, 2026)

Synergistic gel-carrier immobilization strategy for anaerobic ammonia-oxidizing bacteria: Micro-spatial distribution and microbial community synergy - Wenshan He; Guo-hua Liu; Zhen Huang; Mohan Gao; Yang Qin; Suying Ding; Xiao-jun Wang; Yu-qian Shi; Lu Qi; Hongchen Wang (Journal of Environmental Chemical Engineering, 2026)

Mineral-driven accumulation of microbial necromass enhanced humification during composting - Wenjie Chen; Yan Yang; Kui Zhang; Su Chang; Yuan Chang; Ji Li; Xia Liang; Yifan Liu; Long D. Nghiem; Mohan Bai; Huike Ye; Zichao Zhao; et al. (Journal of Environmental Chemical Engineering, 2026)

Whey protein regulation of muscle protein synthesis: From molecular mechanisms to physiological effects - Jiale Wang; Yumeng Zhang; Haokun Kang; Shengyi Zhang; Huiyi Yang; Yijin Wang; Xiqing Yue; Zhenmin Liu; Mohan Li (Food Bioscience, 2026)

Evaporated molecular bilayers strengthen interface reliability of perovskite solar cells - Lianlian Qi; Longjie Deng; Abuduwaili Mijiti; Mohan Sun; Yuhan Liu; Xuan Wu; Guozheng Du; Xiaofeng Li; Li Yang; Jinbao Zhang (Chemical Engineering Journal, 2026)

Straw-Degrading microbiota Exhibit a pivotal ecological function in pathogen elimination for composting with corn straw addition - Qifan Yang; Mohan Bai; Dan Zhang; Xiang Liu; Yinuo Ding; Houyu Li; Yan Xu (Bioresource Technology, 2026)

The effect of swirler structure on the combustion characteristics of ammonia-hydrogen flames in a miniature swirl combustor - Xiao Yang; Keqin Sheng; Mohan Li; Mengyu Wang; Dongtai Han; Xuanqi Liu; Li Yang; Fang Liu (Fuel, 2026)

Regulation of lipid metabolism and flavor formation in Tianfu broiler chickens via the circ_015424/miR-196-1-3p/MOGAT1 axis - Zhi Hu; Jiapeng Chen; Hengyong Xu; Xuyang Ji; Jiajun Zhu; Longge Guo; Xinqi Wang; Yiping Liu; Chaowu Yang; Chunlin Yu; Zengrong Zhang; Mohan Qiu; et al. (Food Chemistry, 2026)

Unusual bending-inducing performance enhancement of flexible blue perovskite light-emitting diodes by dynamic hydrogen bond - Mohan Li; Yamin Tao; Kaiyang Zhang; Qian Miao; Lanlan Zhai; He Huang; Haihong Wen; Guoku Chao; Yun Yang; Jun Zou; Chao Zou (Chemical Engineering Journal, 2026)

Transport of polystyrene microplastics in paddy soils with different chemical conditions: effects of anionic and cationic surfactants - Bingru Yang; Feihong Liu; Yiqun Gong; Mohan Zhao; Husheng Jiang; Wenjing Sang (Journal of Soils and Sediments, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Transport behavior of aged microplastics in unsaturated sandy soil: Impacts of solution chemistry and flow velocity - Mohan Zhao; Jing Miao; Husheng Jiang; Bingru Yang; Wenjing Sang (Process Safety and Environmental Protection, 2026)

Upcycling sediment wastes into S-scheme heterojunctions for efficient photocatalytic tetracycline degradation: Performance, DFT calculations and toxicity assessment - Ni Su; Shuo Yang; Mohan Wang; Yuanyuan Liu; Ruixian Yuan; Hefan Zhang; Zhao Liang; Changyu Lu (Journal of Environmental Management, 2026)

Biodegradable microplastics exert differential impacts from polyethylene on pesticide fate in soil-earthworm systems: insights into degradation selectivity and microbial mechanisms - Dan Yang; Ruiting Dong; Furong Fu; Lixia Zhao; Xiaojing Li; Huike Ye; Mohan Bai; Yang Sun (Environmental Pollution, 2026)

Study on the carbonation environment characteristics of highway tunnels based on long-term field testing - Xingbo Han; Mohan Li; Zhi Chen; Peiyuan Wang; Nianbing Deng; Haiting Yang; Fei Ye (Tunnelling and Underground Space Technology, 2025)

Transport of polystyrene microplastics in saturated and unsaturated paddy soils: Effect of freeze-thaw cycles under different physicochemical conditions - Husheng Jiang; Ming Wu; Wenxin Gao; Mohan Zhao; Bingru Yang; Wenjing Sang (Journal of Environmental Chemical Engineering, 2025)

Suppression of halogen migration and defect passivation driven by electrostatic interaction for high performance quasi-2D pure-blue perovskite LED - Minfei Lan; Ruoyan Liu; Mohan Li; Zhiying Guo; Weiping Mo; Zhijun Liu; Lanlan Zhai; Qian Miao; He Huang; Guoku Chao; Yun Yang; Lijie Zhang; et al. (Chemical Engineering Journal, 2025)

Unveiling the mechanisms of metolachlor biodegradation and physiological adaptations in Penicillium oxalicum MetF1 - Pengtao Chen; Huike Ye; Lixia Zhao; Xiaojing Li; Mohan Bai; Yongtao Li; Liping Weng; Yang Sun (Bioresource Technology, 2025)

Different distribution patterns and potential risks of pesticide residues between soils and sediments: a case study in Lake Taihu Ecological Conservation Area - Yuyang Hao; Mohan Bai; Lanqing Sun; Shuo Yang; Chunyu Wang; Qing X. Li; Bruce D. Hammock; El-Sayed A. El-Sheikh; Ting Xu (Environmental Monitoring and Assessment, 2025)

Experimental and numerical investigation of the effect of hydrogen addition on the stability limits and emission characteristics of ammonia combustion in a small-scale swirl burner - Xiao Yang; Lengjing Li; Mohan Li; Keqin Sheng; Mengyu Wang; Xuanqi Liu; Qingxiang Wang; Yanqun Zhu; Li Yang; Fang Liu (Chemical Engineering Journal, 2025)

Engineering robust, hierarchical, and biodegradable cellulose foams for smart packaging - Aijun Xie; Haishun Du; Sonali Mohapatra; Kun Liu; Jisheng Yang; Jee-Hwan Oh; Mohan Li; Yumeng Zhang; Mengge Gao; Sundaram Gunasekaran; Xuejun Pan (Chemical Engineering Journal, 2025)

A robust two-stage framework for maize above-ground biomass prediction integrating spectral remote sensing and allometric growth model - Mohan Yang; Qiang Wu; Jianbo Qi; Guijun Yang; Zanpu Wang; Zhenyu Wang; Jun Zhang; Hao Yang; Jinpeng Cheng; Shuping Xiong; Xinming Ma (Computers and Electronics in Agriculture, 2025)

Fifteen years observations of detrital 10Be after the Wenchuan earthquake: Insights into landslide sediment transport following a large-magnitude seismic event - Wenxin Wang; Wei Wang; Jing Liu-Zeng; Vincent Godard; Jinyu Zhang; Jinglei Yang; Xucong Zheng; Zijun Wang; Kejia Xie; Mohan Li (Geomorphology, 2025)

Enhancing tetracycline removal: Performance and mechanisms of interspecies electron transfer in microbial consortia - Zhennan Wang; Huike Ye; Xiaojing Li; Yang Sun; Lixia Zhao; Yali Chen; PinPin Yang; Liping Weng; Mohan Bai (Journal of Hazardous Materials, 2025)

Preharvest and Postharvest γ-Aminobutyric Acid Treatment Enhance Quality and Shelf Life in Strawberry (Fragaria × ananassa) Fruits - Ying Zheng; Xiaohuan Han; Yang Zhang; Weiwen Qiu; Tao Tao; Yuting Xu; Mohan Li; Xingbin Xie; Peipei Sun; Guanghui Zheng; Congbing Fang; Jing Zhao (Journal of Plant Growth Regulation, 2025)

Plastic Biofilms as Hotspots of Nitrogen Cycling in Estuarine Ecosystems: Comparative Ecological, Genomic, and Transcriptomic Analysis Across Substrates - Xinrong Huang; Leyang Yang; Shuyidan Zhou; Lei Zhong; Guanghui Xu; Mohan Bi; Xiaoru Yang; Xiaoxuan Su; Matthias C. Rillig (Global Change Biology, 2025)
Biofilms represent a ubiquitous microbial lifestyle that facilitates colonization, symbiosis, and nutrient cycling, shaping environmental chemical transformations. In the Anthropocene, the proliferation of artificial surfaces, particularly plastics, has introduced novel and artificial ecological niches for microbial colonization. However, the biogeochemical potential of biofilms on these emerging artificial substrates remains largely unknown. Here, using 15 N tracing, amplicon, metagenome, and metatranscriptomic sequencing, we explore nitrogen (N) potential biogeochemistry across artificial and natural biofilms as well as the bulk seawater. Our results reveal that plastic biofilms exhibit enhanced N transformation potential, including elevated nitrification (2~45‐fold), denitrification (5~44‐fold), and N 2 O production (3~13‐fold) rates, compared to natural biofilms and ambient seawater. This functional shift corresponds to distinct microbial community structures, driven by active N‐cycling taxa and metabolic pathway reconfigurations on plastic surfaces. We also observe that carbohydrate metabolism pathways, such as glycolysis and the pentose phosphate pathway, were highly expressed in plastic biofilms, with transcriptional levels of glk (encoding glucokinase) and PGK (encoding phosphoglycerate kinase) increased by 6‐ and 2‐fold, respectively. Our findings depict the role of plastic biofilms as active participants in estuarine N cycling and underscore the broader implications of plastic pollution on ecosystem biogeochemistry.

Development of a 2-DoF nonlinear fuzzy PI–PD controller for a tractor active suspension system - Debdoot Sain; B.M. Mohan; Jung-Min Yang (Computers and Electronics in Agriculture, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Anti-obesity potential of chickpea fermented by Lactiplantibacillus sp. (PMS-A6) from salted oyster: UPLC-ESI-Q-TOF-MSE profiling and in-vitro/in-vivo validation - Harshavardhan Mohan; Pavithra Muthukumar Sathya; Satabdi Acharya; Jung-Hee Park; Vaikundamoorthy Ramalingam; Hee-Jong Yang; Do-Youn Jeong; Byung-Taek Oh (Food Research International, 2025)

Tailoring hetero-precursor transformation for simultaneous surface-coating and subsurface-doping of Ni-rich layered oxide cathodes - Junfan Zhang; Ran Wang; Kunkun Guo; Mohan Yang; Zenan Zhao; Jing Wang; Qi Liu; Lai Chen; Ning Li; Yuefeng Su; Feng Wu; Guoqiang Tan (Chemical Engineering Journal, 2025)

miR-24-3p inhibits lipid synthesis and progesterone secretion in chicken granulosa cells via ERK1/2 signaling pathway - Yanrong Gong; Zhongzhen Lin; Hao Sun; Chunlin Yu; Mohan Qiu; Xia Xiong; Lingqian Yin; Donghao Zhang; Yan Wang; Chaowu Yang; Yiping Liu (Theriogenology, 2024)

Discovering the role of fairy ring fungi in accelerating nitrogen cycling to promote plant productivity in grasslands - Mohan Liu; Yuqi Wei; Lu Lian; Junling Zhang; Nan Liu; Gail W.T. Wilson; Matthias C. Rillig; Shangang Jia; Gaowen Yang; Yingjun Zhang (Soil Biology and Biochemistry, 2024)

Tetracycline removal by immobilized indigenous bacterial consortium using biochar and biomass: Removal performance and mechanisms - Xinping Yu; Mohan Bai; Xiaojing Li; Pinpin Yang; Qiuzhen Wang; Zhennan Wang; Liping Weng; Huike Ye (Bioresource Technology, 2024)

Synthesis of CuInS2 Quantum Dots Modified with Alanine for Sensitive and Selective Detection of Pb2+ and Cysteine - Zixuan Jia; Menghan Chen; Mohan Yang; Shenna Chen; Xuhong Zhang (Journal of Fluorescence, 2024)

Nutritional evaluation of almond protein-whey protein double system and its effect on lipid metabolism in HepG2 cells - Xinyu Shen; Jinzhu Yue; Jia Fu; Yangze Guo; Huiyi Yang; Qiumei Liu; Nuo Xu; Xiqing Yue; Mohan Li (Food Bioscience, 2024)

Transcriptome Sequencing and Mass Spectrometry Reveal Genes Involved in the Non-mendelian Inheritance-Mediated Feather Growth Rate in Chicken - Mohan Qiu; Zengrong Zhang; Shiliang Zhu; Siyang Liu; Han Peng; Xia Xiong; Jialei Chen; Chenming Hu; Li Yang; Xiaoyan Song; Bo Xia; Chunlin Yu; et al. (Biochemical Genetics, 2024)
The feather growth rate in chickens included early and late feathering. We attempted to characterize the genes and pathways associated with the feather growth rate in chickens that are not in agreement with Mendelian inheritance. Gene expression profiles in the hair follicle tissues of late-feathering cocks (LC), early-feathering cocks (EC), late-feathering hens (LH), and early-feathering hens (EH) were acquired using RNA sequencing (RNA-seq), mass spectrometry (MS), and quantitative reverse transcription PCR (qRT‑PCR). A total of 188 differentially expressed genes (DEGs) were ascertained in EC vs. LC and 538 DEGs were identified in EH vs. LH. We observed that 14 up-regulated genes and 9 down-regulated genes were screened both in EC vs. LC and EH vs. LH. MS revealed that 41 and 138 differentially expressed proteins (DEPs) were screened out in EC vs. LC and EH vs. LH, respectively. Moreover, these DEGs and DEPs were enriched in multiple feather-related pathways, including JAK-STAT, MAPK, WNT, TGF-β, and calcium signaling pathways. qRT-PCR assay showed that the expression of WNT8A was decreased in LC compared with EC, while ALK and GRM4 expression were significantly up-regulated in EH relative to LH. This study helps to elucidate the potential mechanism of the feather growth rate in chickens that do not conform to genetic law.

Proteomic and phosphoproteomic reveal immune-related function of milk fat globule membrane in bovine milk of different lactation periods - Xue Bai; Jingwen Shang; Xueyan Cao; Mohan Li; Hong Yu; Chunshuang Wu; Mei Yang; Xiqing Yue (Food Chemistry, 2024)

Green synthesis of graphene for targeted recovery of silver from photovoltaic waste - Muhammad Adeel Zafar; Yang Liu; Mohan V. Jacob (Chemosphere, 2024)

Non-sealed water hastens the efficiency of microbial electrochemical remediation system - Iranzi Emile Rushimisha; Huike Ye; Side Yang; Xin Yu; Mohan Bai; Yali Chen; Benjamin Manirakiza; Xiaojing Li; Yongtao Li (Journal of Cleaner Production, 2024)

Revealing the diversity of endogenous peptides and parent proteins in human colostrum and mature milk through peptidomics analysis - Jianting Ning; Mei Yang; Qing Zhu; Xiaoyu Liu; Mohan Li; Xue Luo; Xiqing Yue (Food Chemistry, 2024)

Enhancing selective ammonium transport in membrane electrochemical systems - Kai Yang; Mohan Qin (Water Research, 2024)

Fulvic acid more facilitated the soil electron transfer than humic acid - Side Yang; Kai Wang; Xin Yu; Yan Xu; Huike Ye; Mohan Bai; Lixia Zhao; Yang Sun; Xiaojing Li; Yongtao Li (Journal of Hazardous Materials, 2024)

Suppressing interfacial nonradiative recombination by alkali hydroxides for efficient blue perovskite light-emitting diodes - Yingyu Wang; Yuting Xu; Jieyu Yun; Qiuting Cai; Lanlan Zhai; Dicai Zhuang; Guanghong Yang; He Huang; Mohan Li; Yun Yang; Lijie Zhang; Chao Zou (Chemical Engineering Journal, 2024)

Thiram exposure induces tibial dyschondroplasia in broilers via the regulation effect of circ_003084/miR-130c-5p/BMPR1A crosstalk on chondrocyte proliferation and differentiation - Hengyong Xu; Yuru Jiang; Yuxiang Lu; Zhi Hu; Ranran Du; Yuxin Zhou; Yiping Liu; Xiaoling Zhao; Yaofu Tian; Chaowu Yang; Zengrong Zhang; Mohan Qiu; et al. (Journal of Hazardous Materials, 2024)

Facile preparation of sodium alginate/poly(vinyl alcohol)/graphite hybrid porous hydrogel for efficient solar desalination - Mohan Yang; Lei Zhang; Dezhan Ye; Yongqiang Dong; Yanhu Zhan; Xiancai Jiang (Chemical Engineering Journal, 2024)

Discovery of imidazopyridine-pyrazoline-hybrid structure as SHP-1 agonist that suppresses phospho-STAT3 signaling in human breast cancer cells - Min Hee Yang; Gautam Sethi; Akshay Ravish; Arun Kumar Mohan; Vijay Pandey; Peter E. Lobie; Shreeja Basappa; Basappa Basappa; Kwang Seok Ahn (Chemico-Biological Interactions, 2023)

Macrofungi promote SOC decomposition and weaken sequestration by modulating soil microbial function in temperate steppe - Mohan Liu; Yuqi Wei; Lu Lian; Bin Wei; Yixian Bi; Nan Liu; Gaowen Yang; Yingjun Zhang (Science of The Total Environment, 2023)

Label-free quantitative proteomic analysis of milk fat globule membrane proteins in porcine colostrum and mature milk - Huiwen Zhao; Mohan Li; Qing Zhu; Aicheng Liu; Jiayang Bi; Zhizhong Quan; Xue Luo; Yan Zheng; Ning Yang; Xiqing Yue; Xueyan Cao (Food Chemistry, 2023)

Effect of microplastics on the degradation of tetracycline in a soil microbial electric field - Kai Wang; Side Yang; Xin Yu; Yonghong Liu; Mohan Bai; Yan Xu; Liping Weng; Yongtao Li; Xiaojing Li (Journal of Hazardous Materials, 2023)

Nemopilema nomurai jellyfish venom attenuates phenotypic modulation of PDGF BB-induced vascular smooth muscle cells and κ-carrageenan-induced rat tail thrombosis - Hyeryeon Yang; Seongkyeong Bae; Du Hyeon Hwang; Ramachandran Loganathan Mohan Prakash; Jong-Hyun Kim; Il-Hwa Hong; Woo Hyun Kim; Il Rae Rho; Euikyung Kim; Changkeun Kang (Toxicon, 2023)

Mitigation effects and microbial mechanism of two ecological earthworms on the uptake of chlortetracycline and antibiotic resistance genes in lettuce - Side Yang; Chenxi Lu; Cheng Qin; Chang Lu; Zheng Pan; Lixia Zhao; Mohan Bai; Xiaojing Li; Yang Sun; Liping Weng; Yongtao Li (Science of The Total Environment, 2023)

Nitrite sensor using activated biochar synthesised by microwave-assisted pyrolysis - Scarlett Allende; Yang Liu; Muhammad Adeel Zafar; Mohan V. Jacob (Waste Disposal & Sustainable Energy, 2023)
Developing applications for the by-products obtained from waste processing is vital for resource recovery. The synthesis of ZnCl 2 -activated biochar with high electrocatalytic activity was carried out by the microwave-assisted pyrolysis of pineapple peel and subsequent chemical activation process. Activated biochar is employed in the electrochemical sensing of nitrite by drop casting in a glassy carbon electrode (GCE). The activated biochar exhibited a stacked carbon sheet, 254 m 2 g −1 Brunauer, Emmett and Teller (BET) surface area, 0.076 cm 3 g −1 pore volume, 189.53 m 2 g −1 micropore area and oxygen-containing functional groups. The electrochemical impedance spectroscopy of the modified GCE showed a reduced charge transfer resistance of 61%. This is crucial to determine the electrochemical properties of biochar. The sensor showed a significant current response and an excellent limit of detection of 0.97 µmol L −1 . The modified-activated biochar electrochemical sensor demonstrated high selectivity, reproducibility (RSD=2.4%), and stability (RSD=2.6%). Graphical abstract

RNA sequencing reveals lncRNA-mediated non-mendelian inheritance of feather growth change in chickens - Mohan Qiu; Chunlin Yu; Shiliang Zhu; Siyang Liu; Han Peng; Xia Xiong; Jialei Chen; Xiaosong Jiang; Huarui Du; Qingyun Li; Zengrong Zhang; Chaowu Yang (Genes & Genomics, 2022)
Background Long non-coding RNAs (lncRNAs) play an essential role in biological processes. However, the expression patterns of lncRNAs that regulate the non-Mendelian inheritance feather phenotypes remain unknown. Objective This study aimed to compare the expression profiles of lncRNAs in the follicles of the late-feathering cocks (LC) and late-feathering hens (LH) that followed genetic rules and the early-feathering hen (EH) and early-feathering cock (EC) that did not conform to the genetic laws. Methods We performed RNA sequencing and investigated the differentially expressed lncRNAs (DElncRNAs) between the early- and late-feathering chickens, which function by cis-acting or participate in the competing endogenous RNA (ceRNA) network. Results A total of 53 upregulated and 43 downregulated lncRNAs were identified in EC vs. LC, and 58 upregulated and 109 downregulated lncRNAs were identified in EH vs. LH. The target mRNAs regulated by lncRNAs in cis were enriched in the pentose phosphate pathway, TGF-β signaling pathway and Jak-STAT signaling pathway in EC vs. LC and were associated with the TGF-β signaling pathway, Wnt signaling pathway, p53 signaling pathway and Jak-STAT signaling pathway in EH vs. LH. In addition, the lncRNA-mediated ceRNA regulatory pathways of hair follicle formation were mainly enriched in the TGF-β signaling pathway, Wnt signaling pathway, melanogenesis, and calcium signaling pathways. The levels of ENSGALG00000047626 were significantly higher in the late-feathering chickens than in the early-feathering chickens, which regulated the expression of SSTR2 by gga-miR-1649-5p. Conclusion This study provides a novel molecular mechanism of lncRNA’s response to the feather rate that does not conform to the genetic laws in chickens.

High-throughput sequencing revealed the expression profile and potential key molecules of the circular RNAs involved in the process of hypoxic adaptation in Tibetan chickens - Zengrong Zhang; Mohan Qiu; Huarui Du; Qingyun Li; Wu Gan; Xia Xiong; Chunlin Yu; Han Peng; Bo Xia; Xiaoyan Song; Li Yang; Chenming Hu; et al. (Biologia, 2021)

Long Non-coding RNA Expression Profile in Broiler Liver with Cadmium-Induced Oxidative Damage - Chunlin Yu; Chaowu Yang; Xiaoyan Song; Jingjing Li; Han Peng; Mohan Qiu; Li Yang; Huarui Du; Xiaosong Jiang; Yiping Liu (Biological Trace Element Research, 2021)

Paraburkholderia panacisoli sp. nov., a potentially antagonistic bacterium against the root rot fungal pathogen Cylindrocarpon destructans, isolated from ginseng cultivation soil - Yue Huo; Mohan Chokkalingam; Jong-Pyo Kang; Jong-Chan Ahn; Deok-Chun Yang (Archives of Microbiology, 2020)

Effects of free-range broiler production on vegetation characteristic and soil physicochemical property of the stocking areas in China - Chunlin Yu; Xiaosong Jiang; Huarui Du; Qingyun Li; Zengrong Zhang; Mohan Qiu; Tianbao Chen; Bo Xia; Xiaoyan Song; Chenming Hu; Xia Xiong; Li Yang; et al. (Agroforestry Systems, 2020)

User-Guided Segmentation of Multi-modality Medical Imaging Datasets with ITK-SNAP - Paul A. Yushkevich; Artem Pashchinskiy; Ipek Oguz; Suyash Mohan; J. Eric Schmitt; Joel M. Stein; Dženan Zukić; Jared Vicory; Matthew McCormick; Natalie Yushkevich; Nadav Schwartz; Yang Gao; et al. (Neuroinformatics, 2019)

Paenibacillus panacihumi sp. nov., a potential plant growth-promoting bacterium isolated from ginseng-cultivated soil - Chun-Gon Kim; Jong-Pyo Kang; Yue Huo; Mohan Chokkalingam; Yeon-Ju Kim; Dong-Hyun Kim; Deok-Chun Yang (Archives of Microbiology, 2018)

Effects of different fertilizers on growth and nutrient uptake of Lolium multiflorum grown in Cd-contaminated soils - Mohan Liu; Yang Li; Yeye Che; Shaojun Deng; Yan Xiao (Environmental Science and Pollution Research, 2017)

Therapeutic Sesamol Attenuates Monocrotaline-Induced Sinusoidal Obstruction Syndrome in Rats by Inhibiting Matrix Metalloproteinase-9 - Srinivasan Periasamy; Dur-Zong Hsu; Shin-Yi Chen; Shan-Shan Yang; Victor Raj Mohan Chandrasekaran; Ming-Yie Liu (Cell Biochemistry and Biophysics, 2011)

Exploitation of the late flowering species Brassica oleracea L. for the improvement of earliness in B. napus L.: an untraditional approach - M. Habibur Rahman; Rick A. Bennett; Rong-Cai Yang; Berisso Kebede; Mohan R. Thiagarajah (Euphytica, 2011)

Detecting and estimating segregation distortion and linkage between glufosinate tolerance and blackleg resistance in Brassica napus L. - Rong-Cai Yang; Mohan R. Thiagarajah; Vipan K. Bansal; Gary R. Stringam; M. Habibur Rahman (Euphytica, 2006)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)